2003
DOI: 10.1007/s00586-003-0658-0
|View full text |Cite
|
Sign up to set email alerts
|

Extradural lumbosacral cavernous hemangioma

Abstract: Purely extradural cavernous hemangiomas of the spinal canal are extremely rare. Their occurrence at the lumbosacral level is a true exception. We describe a case of lumbosacral extradural hemangioma and review the behaviour and MR imaging characteristics of these lesions. Cavernous hemangioma should be considered in the differential diagnosis of an enhancing extradural periradicular mass causing chronic lumbar radiculopathy especially in fertile women. Lumbar extradural hemangiomas appear and behave differentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Bleeding is seldom a problem with intramedullary cavernous angiomas during surgery, however, severe intraoperative bleeding may occur in spinal epidural cavernous angiomas [17]. Therefore, adequate exposure is necessary to prevent massive intraoperative bleeding, especially in the lumbar lesions, where the lesion resembles a disc fragment [26,28]. In our series, complete surgical removal was achieved in all cases and confirmed by postoperative MRI.…”
Section: Clinical and Surgical Featuresmentioning
confidence: 57%
See 2 more Smart Citations
“…Bleeding is seldom a problem with intramedullary cavernous angiomas during surgery, however, severe intraoperative bleeding may occur in spinal epidural cavernous angiomas [17]. Therefore, adequate exposure is necessary to prevent massive intraoperative bleeding, especially in the lumbar lesions, where the lesion resembles a disc fragment [26,28]. In our series, complete surgical removal was achieved in all cases and confirmed by postoperative MRI.…”
Section: Clinical and Surgical Featuresmentioning
confidence: 57%
“…They are usually confined to two or more spinal levels, and have an oval shape, sometimes flattened toward the spinal cord rather than distorting it [15,25]. SSECA are well delineated and often have a capsule or pseudo-capsule [3,26]. Lesions of the lumbosacral region are usually round or ovoid, located in the ventral and/or ventro-lateral epidural space or just within the peri-radicular space [9,26,28] as in our case 3 and 8.…”
Section: Gross Featurementioning
confidence: 76%
See 1 more Smart Citation
“…It is very difficult to diagnose before surgery. A study by Tekkök et al 13) reported on 14 surgical resections of cavernous hemangioma, none of which was diagnosed preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar extradural hemangiomas behave differently, not only from intramedullary cavernous hemangiomas but also from extradural cavernomas of other spinal locations. [9] Purely extradural hemangiomas should be included in the differential diagnosis of lumbar extradural soft-tissue lesions. [10]…”
Section: Discussionmentioning
confidence: 99%